The native speaker and the mother tongue - Love, Nigel; Ansaldo, Umberto (ELSEVIER SCI LTD, 2010)
This article presents a historical account of the role and function in linguistic theorising of the concepts “native speaker” and “mother tongue”, and serves to introduce a number of articles (Language Sciences vol. 32 no. 6) raising questions about various aspects of the idealised monolingualism that underlies much modern linguistics.